2017
DOI: 10.5539/mas.v11n10p74
|View full text |Cite
|
Sign up to set email alerts
|

Potency of Bacillus spp from Potato Rhizosphere as Active Ingredients for Biostimulant Formulation

Abstract: Bacteria that colonized plant roots can be identify, characterify and tested for their ability to stimulate plant growth. The purpose of this research is to know the ability of Bacillus spp bacteria as active ingredient of biostimulant formulation which aims to stimulate the growth of plants. Bacillus spp bacteria derived from rooting potato plants tested its ability to dissolve phosphate, N fixation, producing IAA, GA, siderophore and HCN. The results showed different abilities in producing growth-promoting c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
1
0
1
Order By: Relevance
“…RJ1T bacterial isolate is a gram-positive bacterium with a coccus cell shape (Figure 6). Research by Kesaulya et al (2017) confirmed auxin production from several gram-positive bacteria ranging from 0.39-5.8 mg.L -1 . Actinomecetas bacteria can produce IAA ranging from 0.33-36 mgL .-1 (Fatmawati et al 2019).…”
Section: Discussionmentioning
confidence: 94%
“…RJ1T bacterial isolate is a gram-positive bacterium with a coccus cell shape (Figure 6). Research by Kesaulya et al (2017) confirmed auxin production from several gram-positive bacteria ranging from 0.39-5.8 mg.L -1 . Actinomecetas bacteria can produce IAA ranging from 0.33-36 mgL .-1 (Fatmawati et al 2019).…”
Section: Discussionmentioning
confidence: 94%
“…A desirable characteristic for PGPR is the capacity to produce phytohormones, like auxins. Several species of Bacillus have been reported to produce auxins (Calvo et al, 2010;Kesaulya et al, 2017). Idris et al, (2007) have shown that mutants of B. amyloliquefaciens FZB42 with diminished levels of IAA production were less efficient in promoting plant growth.…”
Section: Resultsmentioning
confidence: 99%
“…Pupuk organik cair dapat dibuat dari bahanbahan organik disekitar lingkungan tempat tinggal, dapat berupa sampah organik rumah tangga, limbah pertanian dan kotoran ternak, hal ini sesuai dengan pernyataan Nassaruddin dan Rosmawati (2011) Sumber bahan baku pupuk organik tersedia dimana saja dengan jumlah yang melimpah yang semuanya dalam bentuk limbah, baik limbah rumah tangga, rumah makan, pasar pertanian, peternakan, maupun limbah organik jenis lain. Revitalisasi pemulihan dan peningkatan produktivitas lahan secara berkelanjutan dapat dilakukan dengan meningkatkan peranan pupuk organik cair yang diperkaya dengan mikroba plant promoting rhizobacteria (PGPR) sebagai biostimulan (Kesaulya 2015;Kesaulya et al, 2015aKesaulya et al, , 2015bKesaulya et al, , 2015cKesaulya et al, 2017). Mikroba yang terdapat pada pupuk organik cair dapat berpengaruh terhadap proses fisiologis dan metabolisme tanaman serta mendukung kesuburan tanah (Nardy et al, 2009).…”
unclassified